Corrosion control of magnesium for stent applications - Elmrabet, Nabila Mustafa (2017)
Biomaterials used for implants may be metallic, ceramic, polymeric or composite. Currently, metals that are gradually broken down in the body have been attracting much attention, as a new generation of biodegradable implants. Magnesium (Mg) and related alloys are promising candidates for degradable biomaterials, comprising temporary mechanical properties with biological acceptance to the human body. However, the target periods set clinically, with respect to the practical uses of Mg for biodegradable stents, have yet to be achieved. Hence, improved understanding of the corrosion behaviour of Mg in the biological environment is needed. Novel Mg narrow walled minitubes, for degradable stent applications, have been produced using radio frequency magnetron sputtering (RF-MS) physical vapour deposition (PVD). The microstructural development of the as-deposited minitubes have been investigated, as a function of annealing temperature, using the combined complementary analytical techniques of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffractometry (XRD) and microhardness indentation. The as-deposited minitubes exhibited columnar grain structures with high levels of porosity, but were very brittle. Slight alteration to the crystal structure, from columnar to more isotropic grain growth, was demonstrated at elevated temperature, along with increasing material densification, hardness and corrosion resistance. It is suggested that stabilisation of the columnar grains and the formation of oxide layers during the sequential Mg-layer deposition process, acted as a barrier, preventing the development of a fully dense, equiaxed structures. The onset and development of Mg corrosion may be addressed by the use of coatings or near surface modification processes. Accordingly, the corrosion resistance of ~ 1-2 µm thick Al coatings, deposited by RF-MS on polished Mg surfaces, within Ar and Ar/H2 environments, were appraised. The coatings were heat-treated at 300°C and 450°C, with the aim of inducing the formation of bioinert Al2O3, and samples were corroded within phosphate buffered saline (PBS) solution at 37°C to mimic the biological environment. Both as-deposited and heat-treated coatings were found to delay the onset of corrosion, but showed higher initial corrosion rates, once established, as compared to the polished Mg surfaces. Slight improvement in coating performance was achieved through the addition of H2 to the system, which acted to inhibit Al-Mg alloying and enhance Al2O3 formation. However, localized accelerated corrosion associated with substrate polishing damage emphasised the need for improved process control and coating uniformity. Si-H coatings deposited on Mg surfaces within Ar/H2 ambient using a PVD technique was also investigated. The as-deposited coatings comprised dense, crack-free amorphous a-Si-H layers with thickness of ~ 1 µm. Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analyses provided evidence for the presence of SiH2 as well as SiOx. The corrosion resistance of a-Si-H coated Mg increased significantly in contact with PBS, in both electrical and immersion tests, due to improved coverage of the substrate. The effect of rapid thermal processing techniques on the corrosion resistance of Mg surfaces was also investigated. Mg surfaces treated by large area electron beam (LAEB) irradiation showed refinement of the surface grain structure, with increased grain boundary delineation, although localised ablation, roughness and crater formation increased with increasing cathode voltage and number of pulses. The corrosion potential and corrosion rate of LAEB modified surfaces generally increased with increase the energy imparted to the surface. The extended corrosion performance of low energy EB processed surfaces, under immersion testing was consistent with the trend of improved corrosion resistance during the early stages of immersion in PBS. However, surfaces over-processed at high energies experienced higher corrosion rates in both potentiodynamic and immersion testing, due to the development of inclusions, craters and cracks on the modified surface. Further, Mg surfaces, modified by laser surface melting (LSM) under conditions of low energy laser irradiation, experienced rapid melting, causing surface smoothening and grain refinement centred along the laser beam tracks, whilst coarser grains decorated the overlapping regions, due to the Gaussian shape of the laser beam profile. More uniform surface processing was achieved by increasing the laser beam spot size, which acted to improve the corrosion resistance of Mg. Under high energy LSM processing conditions, Mg surfaces showed conventional laser melting rippled patterns, along with craters and cracks, and the redeposition of MgO particles, causing an increase in surface roughness and corrosion rate. The corrosion performance under immersion testing showed the corrosion rate similar to that of the original polished Mg samples, due to non-uniform surface modification and the mixed development of fine and coarser grains. However, observation revealed that refined grain regions along the centre of the laser tracks were able to resist corrosion for longer times. Generally, annealed Mg-minitubes produced by PVD, and the near surface modification of Mg by EB and LSM, showed that fine grained Mg can affect the electrochemical response of Mg within the physiological environment, due to the rapid, enhanced development of the passivation layer, promoted by improvements in surface homogeneity and an increase in grain boundary density.